2022
DOI: 10.32607/actanaturae.11427
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Detection in the Study of Free-Radical Reactions. Part 2. Luminescent Additives That Increase the Chemiluminescence Quantum Yield

Abstract: The present review examines the use of chemiluminescence detection to evaluate the course of free radical reactions in biological model systems. The application of the method is analyzed by using luminescent additives that enhance the luminescence thanks to a tripletsinglet transfer of the electron excitation energy from radical reaction products and its emission in the form of light with a high quantum yield; these additives are called chemiluminescence enhancers or activators. Examples of these substances ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…In Lin HC [12], when studying super weak luminescence in a mixture of Fenton with ortho-chlorophenol, the result of work [7] was confirmed that singlet oxygen is luminescent agent. In Romodin LA [13], chemiluminescence was considered in the study of free radical reactions, kinds of luminescent additives were discussed to increase the quantum yield of chemiluminescence. Research continues on Fenton like reactions [14] and new methods of chemiluminescence analysis in the Fenton reaction [15].…”
Section: Introductionmentioning
confidence: 99%
“…In Lin HC [12], when studying super weak luminescence in a mixture of Fenton with ortho-chlorophenol, the result of work [7] was confirmed that singlet oxygen is luminescent agent. In Romodin LA [13], chemiluminescence was considered in the study of free radical reactions, kinds of luminescent additives were discussed to increase the quantum yield of chemiluminescence. Research continues on Fenton like reactions [14] and new methods of chemiluminescence analysis in the Fenton reaction [15].…”
Section: Introductionmentioning
confidence: 99%